2020
DOI: 10.3389/fendo.2020.00142
|View full text |Cite
|
Sign up to set email alerts
|

Timing of the Infancy-Childhood Growth Transition in Rural Gambia

Abstract: The Karlberg model of human growth describes the infancy, childhood, and puberty (ICP) stages as continuous and overlapping, and defined by transitions driven by sequential additional effects of several endocrine factors that shape the growth trajectory and resultant adult size. Previous research has suggested that a delayed transition from the infancy to the childhood growth stage contributes to sub-optimal growth outcomes. A new method developed to analyze the structure of centile crossing in early life has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Thus, any continued challenges (such as those provoked by under nutrition and infection) to homeostasis during the development period may trigger epigenetic programming and shift the timing and duration of these periods of growth. The study reported by Bernstein et al (91) has revealed an accelerated transition to a childhood pattern of growth in Gambian compared to UK infants. A later transition, observed in UK infants, extends the high growth rate experienced during the infancy stage.…”
Section: Discussionmentioning
confidence: 90%
“…Thus, any continued challenges (such as those provoked by under nutrition and infection) to homeostasis during the development period may trigger epigenetic programming and shift the timing and duration of these periods of growth. The study reported by Bernstein et al (91) has revealed an accelerated transition to a childhood pattern of growth in Gambian compared to UK infants. A later transition, observed in UK infants, extends the high growth rate experienced during the infancy stage.…”
Section: Discussionmentioning
confidence: 90%
“…If the global issue of stunting is to be addressed, its dynamic causes must be identified and explored. From a mechanistic perspective, it is clear that repeated rounds of growth faltering (e.g., resulting from high morbidity, undernutrition, repeated seasonal pressures, or other adverse conditions) could potentially (a) deplete resources available to support growth (Stearns, 1989), and (b) signal a “high risk” environment to the developing individual, potentially impacting growth patterns and health in both the short‐ and long‐term (Bernstein et al, 2020; Gluckman et al, 2005). Close analysis of the dynamics of faltering episodes as presented here can help tease apart the causes and consequences of faltering, shed light on how those episodes contribute to the broader state of faltering from a “potential” trajectory identified by prior methods, and may provide valuable insight regarding the efficacy of interventions designed to improve growth and growth outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In the present analysis, it was impossible to determine the ICT for almost a quarter (161/657) of the study children. Recently it was proposed to use the infancy-childhood transition of weight for age z-score, based on the Widdowson and Cambridge Infant Growth Study (CIGS) (30,31), however this model requires validation and endocrine and evolutionary collateral.…”
Section: Limitationsmentioning
confidence: 99%